The Four Pillars for Successful Regenerative Therapy in Endodontics: Stem Cells, Biomaterials, Growth Factors, and Their Synergistic Interactions - C. Brizuela; George T.-J. Huang; A. Diogenes; T. Botero; M. Khoury (Stem Cells International)
Endodontics has made significant progress in regenerative approaches in recent years, thanks to advances in biologically based procedures or regenerative endodontic therapy (RET). In recent years, our profession has witnessed a clear conceptual shift in this therapy. RET was initially based on a blood clot induced by apical bleeding without harvesting the patient’s cells or cell-free RET. Later, the RET encompassed the three principles of tissue engineering, stromal/stem cells, scaffolds, and growth factors, aiming for the regeneration of a functional dentin pulp complex. The regenerated dental pulp will recover the protective mechanisms including innate immunity, tertiary dentin formation, and pain sensitivity. This comprehensive review covers the basic knowledge and practical information for translational applications of stem cell-based RET and tissue engineering procedures for the regeneration of dental pulp. It will also provide overall information on the emerging technologies in biological and synthetic matrices, biomaterials, and signaling molecules, recent advances in stem cell therapy, and updated experimental results. This review brings useful and timely clinical evidence for practitioners to understand the challenges faced for a successful cell-based RET and the importance of preserving or reestablishing tooth vitality. The clinical translation of these current bioengineering approaches will undoubtedly be beneficial to the future practice of endodontics.